Broken basket conundrum - Vigneswara Srinivasan Venkatachalapathy Sockkalingam; Datson George Palathullil; Vijay Radhakrishnan; George Abraham Palathullil (African Journal of Urology, 2020)
Abstract Background Broken basket during retrograde intrarenal surgery (RIRS) is a known complication. The literature regarding this common complication is limited. We report a case of broken basket and explain the technique by which we retrieved the broken basket fragment that was entrapped around the calculus. We also analyze at the prevention strategies and better management strategies. Case presentation A 62-year-old male underwent RIRS for a 2-cm right renal lower calyceal calculus. A tipless nitinol stone basket got broken and distal part got entrapped around the calculus when basketing was attempted. We proceeded with stone fragmentation by RIRS. After complete stone fragmentation, another tipless nitinol stone basket was used to grab the broken tip of distal basket fragment which was lying in the renal pelvis. The broken basket fragment could be retrieved out in toto. Conclusions Basketing large lower calyceal calculus should be attempted with caution. Partial or complete fragmentation of large calculus is preferable before basketing attempt. If the calculus is entrapped rather than forceful pulling, cutting the basket proximally near to the handle, followed by stone fragmentation, could minimize complications. Locating the broken tip of the basket fragment and grasping it makes the retrieval easier and safer.